2012
DOI: 10.1111/jre.12017
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of microRNAs in RAW264.7 cells treated with a combination of tumor necrosis factor alpha and RANKL during osteoclast differentiation

Abstract: These results suggest that miR-223 and miR-378 may play important roles in osteoclastogenesis, and that miR-21, miR-29b, miR-146a, miR-155 and miR-210 are involved in TNF-α-regulated osteoclast differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 51 publications
4
125
0
Order By: Relevance
“…48 Kopriva et al 49 observed that toll-like receptor 3 activation induces placental miR-210 through hypoxia-inducible factor-1α and the nuclear factor-κB-p50 pathway, leading to a decrease in signal transducer and activator of transcription 6, interleukin-4 induced, and interelukin-4 levels, which may contribute to the development of preeclampsia. In this study, we found that TNF-α significantly increased the expression of miR-210 in HTR-8/ SVneo cells, which is similar to the observation of Kagiya et al 29 in murine macrophage cell line, RAW264.7 cells. Meanwhile, the KCMF1 expression was downregulated on TNF-α treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…48 Kopriva et al 49 observed that toll-like receptor 3 activation induces placental miR-210 through hypoxia-inducible factor-1α and the nuclear factor-κB-p50 pathway, leading to a decrease in signal transducer and activator of transcription 6, interleukin-4 induced, and interelukin-4 levels, which may contribute to the development of preeclampsia. In this study, we found that TNF-α significantly increased the expression of miR-210 in HTR-8/ SVneo cells, which is similar to the observation of Kagiya et al 29 in murine macrophage cell line, RAW264.7 cells. Meanwhile, the KCMF1 expression was downregulated on TNF-α treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Tumor necrosis factor-α (TNF-α) has been reported as one of the regulators of miR-210 in other cell type, 29 and this inflammatory factor increased significantly in the fetal-maternal interface of patients with preeclampsia. [30][31][32][33][34] We treated HTR8/SVneo cells with recombinant human TNF-α and examined miR-210 and KCMF1 levels after 24 hours.…”
Section: Tnf-α Increases Mir-210 Expression But Downregulates Kcmf1mentioning
confidence: 99%
“…miRNA participates in osteogenic differentiation from MSCs (Guo et al, 2011). Up-regulated miR-689 expression is involved in tumor necrosis factor-alpha (TNF-α)/RANKL-regulated osteoclast differentiation (Kagiya and Nakamura, 2013). miR-654-5p may play an important role in osteogenic differentiation from human bone marrow MSCsby directly suppressing themRNA and protein expressions of bone morphogenetic protein 2 (BMP2) by binding to a specific target site (Wei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 cells were tested by FISH analysis and found to be diploid at least on chromosomes 7,8,11,16, and 17, and were kindly provided by Prof. P. Tsichlis (Tufts Medical School, Boston, MA). E. coli-derived LPS (100 ng/ml; O111:B4; catalog no.…”
Section: Cell Culturementioning
confidence: 99%
“…In humans, miR-146a appears to be important in the development of innate immune tolerance observed in leukemic patients (8). Both miRs have attracted particular attention, because they are responsive to a plethora of inflammatory stimuli including TLR ligands, TNFa, IL-1b, type I and type II IFNs, or RANKL in different cell types, including macrophages (9)(10)(11)(12)(13)(14)(15)(16). miR-155 and miR-146a target and repress several downstream TLR4 mediators such as TNF-a, PU.1, SHIP1, SOCS1 and TNFR-associated factor-6, IRAK1, and IRF5, respectively, highlighting their pivotal role in the development of endotoxin tolerance (1).…”
mentioning
confidence: 99%